Prioritas Pengembangan Industri Dengan Pendekatan Competitive Priorities - Trifandi Lasalewo (Department Industrial Engineering, University of Muhammadiyah Malang, 2010)
In the process of developing competitive advantages of industry in one area, it is required that order of priority of industrial development policies be based on certain criteria/dimensions in which this order is based on the orientation and development plan according to the perspective of the stakeholders in that area. The competitive advantages are related to the purposes of industry in achieving its best performance and the strategy to be applied so that an industry possesses characteristics of competitive advantages that can survive/win business competition. As a new area, Gorontalo Province requires a scale of priority that can be made as a reference and industrial development plan in the future. The research model constitutes the results of several models of competitive priorities that have been established in several new industrialized countries; meanwhile the research object was focused on Small Medium Industry (SMIs) considering that SMIs are the biggest industrial group in Gorontalo Province. Based on the survey and results of data processing using. The Law of Comparative Judgment (LCJ) method, there are 7 (seven) dominant dimensions that should be considered in developing industry;namely, Quality, Cost/Price, Delivery, Customer Focus, Flexibility, Innovativeness and MarketOrientation. This order of competitive priorities can also be applied in other areas consideringthat the characters of SMI that are the object of the research are in principle the same as thoseof the SMI in other areas of Indonesia.